Small-Scale Business Leadership in Ethiopia: An Assessment of Financial Bureau Opportunities in Yayu Woreda - Satya Narayan Singh (Business Ethics and Leadership)
The present research paper highlights small-scale business leadership in Ethiopia to assess the financial bureau in Yayu Woreda of Ilu Abba Bora Zone of Oromia regional state of Ethiopia. The other allied purpose relates to evaluating the budgetary performance of the Yayo Woreda finance office in the Ilu Abba Bora Zone. The sampling technique is based on simple random sampling, and scientifically there were 100 samples of respondents taken from approximately one thousand and three hundred and seventy-three employees in the woreda. The representative samples were included one head office person, the council head of the budget and finance committee, plus the committee members from the Audit Office, Auditor general, deputy auditor general, Audit manager, and the audit team of consolidated financial statements. Additionally, three employees were also included from each sector, such as planners, accountants, and internal auditors, to control appropriate utilization of limited resources and auditing performance for the allocated budget at the woreda finance office. The descriptive survey design was employed in this study, and appropriate data collection methods were used through questionnaires and interviews. However, the secondary data is extracted from the final report and oversight of the written books and brochures. The data were analyzed and interpreted while using an appropriate methodology of concurrent concern. The study established that the budget implementation and its performance have a negative relationship to some extent. It is recommended that the woreda must have to enhance its manpower, particularly in the budget process, to improve budgetary performance, particularly in the aspect of small-scale business leadership.